EFEKTIVITAS PENGGUNAAN GATHER.TOWN TERHADAP WEBINAR PADA MASYARAKAT KOTA BATAM - Mangapul Siahaan; Mikhael Chendra (JURNAL ILMIAH BETRIK, 2023)
: Gather.Town is an application or video game with 8 bit quality that combines video calls with 2D maps that allow users to interact with other people. The problem faced was the covid pandemic which restricted offline seminars so the idea emerged to conduct webinar research and Gather.Town. This study aims to determine the effectiveness of using Gather.Town for Webinars in Batam City Communities. The research model used in this study is the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2), by measuring the dependent and independent variables in the Effectiveness of Using Gather.Town on Webinars on Batam City Communities. Based on the results of this research analysis, it can be concluded that the quantitative analysis of Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions and Hedonic Motivation has a significant effect on Behavioral Intention, while Behavioral Intention has a significant effect on Use Behavior. In the qualitative analysis it can be concluded that Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions and Hedonic Motivation do not significantly influence the Behavioral Intention variable, while Behavioral Intention significantly influences Use Behavior.